PERANAN GURU AGAMA HINDU DALAM MENUMBUHKEMBANGKAN KARAKTER TOLERANSI SISWA DI SMK NEGERI 1 DENPASAR - Ni Putu Ari Setiawati; Ni Komang Sutriyanti; I Gusti Ngurah Triyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Learning in schools are part of efforts to improve the education of human tolerance from an early age. Such as Vocational High School or SMK (Sekolah Menengah Kejuruan), one of them is Vocational High School 1 Denpasar which placed in the center city of Denpasar, in which the students are not only Hindus, but there are Christianity, Moslem, etc. Therefore, tolerance and respect between each other are needed to support the tolerance between religions; then, the role of the teacher is very important in this case because the teacher can build up the character of students in order to have a tolerant character in the school and in the social community later on . The role of Hindus teachers in developing the tolerance character of student, namely through intracurricular activities and extracurricular activities. Both of these activities have a main contribution in the development of the tolerance character of students. The obstacles faced by Hindus teachers in developing the tolerance character of the students are caused by two factors: the first, the internal factor or innate factors, students interest, and emotional that are natural and innate from within students. The second is the external factors (family, school, community, and mass media) based on the outside of students. Thus, the students must be able to sort themselves out and be balanced by the attention of parents and schools so that these obstacles not interfere with the development of the student's character. The efforts made by Hindus teachers to solve these obstacles in developing the tolerance character of studets at SMK Negeri 1 Denpasar are carried out by applying the 3 S Attitude (Senyum, Salam dan Sapa), the habbit of some activities in the classroom, developing the learning atmosphere.